On Exact Series Solution of Strongly Coupled Mixed Parabolic Problems - Vicente Soler; Emilio Defez; M. V. Ferrer; J. Camacho (Abstract and Applied Analysis)
This paper studies the construction of the exact solution for parabolic coupled systems of the type , , , , , and , where , , , and are arbitrary matrices for which the block matrix is nonsingular, and is a positive stable matrix.